Population Analysis and Genetic Structure of Two Kazakh Cattle Breeds Using 150K SNP - Beishova, I. S.; Dossybayev, K. Zh.; Shamshidin, A. S.; Belaya, A. V.; Bissembayev, A. T.; Khamzin, K. P.; Kovalchuk, A. M.; Nametov, A. M. (HAYATI Journal of Biosciences. - 2022, 2022)
Kazakh white-headed and Auliekol breeds are mostly spread through Kazakhstan and are animals with dual purpose productivity directions including meat and milk. Kazakh native cattle breeds are still largely unexplored based on the genetic markers and are of great interest in the country. In this study, we for the first time applied high-density SNP genotyping for two indigenous cattle breeds to study genetic diversity, population structure and relationships with the different foreign breeds. Using of GGP Bovine 150K SNP array the principal component analysis (PCA), populations estimates of the genetic structure (ADMIXTURE), genetic diversity and distances (Fst), and phylogenetic tree showed that the Kazakh white-headed and Auliekol breeds have certain separate genetic structure that differ from European and Russian cattle breeds The two of these Kazakh cattle breeds have their genetic background according to observed results as distinct breeds. The obtained results will be aided in the development breeding system and conservation programs of the Kazakh white-headed and Auliekol breeds of beef cattle in the Kazakhstan. © 2022, Bogor Agricultural University. All rights reserved. Казахская белоголовая и аулиекольская породы наиболее распространены на территории Казахстана и являются животными с двояким направлением продуктивности, в том числе мясным и молочным. Казахские аборигенные породы крупного рогатого скота до сих пор в значительной степени не изучены по генетическим маркерам и представляют большой интерес для страны. В этом исследовании мы впервые применили генотипирование SNP с высокой плотностью для двух местных пород крупного рогатого скота для изучения генетического разнообразия, структуры популяции и взаимоотношений с различными иностранными породами. Использование массива GGP Bovine 150K SNP, анализа главных компонент (PCA), популяционных оценок генетической структуры (ADMIXTURE), генетического разнообразия и расстояний (Fst) и филогенетического древа показало, что казахская белоголовая и аулиекольская породы имеют отдельные генетические особенности. структуры, которые отличаются от европейских и российских пород крупного рогатого скота Две из этих казахских пород крупного рогатого скота имеют свой генетический фон, согласно наблюдаемым результатам, как отдельные породы. Полученные результаты будут использованы при разработке племенной системы и программ сохранения казахской белоголовой и аулиекольской пород мясного скота в Казахстане.
Keywords: импакт-фактор 2022; скопус; зарубежное издание; дальнее зарубежье; научный журнал; генетика животных; зарубежные авторы; скотоводство; казахская белоголовая порода крс; аулиекольская порода крс